Assessment of the benefits of information and communication technologies (ICT) adoption on downstream supply chain performance of the retail industry - Kedar Shiralkar; Arunkumar Bongale; Satish Kumar; Ketan Kotecha; Chander Prakash (Logistics, 2021)
Background: The COVID-19 pandemic-driven supply chain disruptions have pushed supply chain decision-makers in the retail industry to implement information and communication technologies (ICT) to improve the efficiency and resiliency of their supply chain. However, they need some guidance to identify the functional elements of the supply chain for ICT adoption and the benefits of implementing ICT on their supply chain performance. Methods: We conducted an empirical study that provides guidance on the performance benefits of ICT adoption specifically for the downstream supply chain of the retail industry. This study employed the feature engineering technique to prioritize the functional elements of the supply chain to maximize the benefits of ICT adoption on supply chain performance. Results: ICT adoption benefits the retail industry's overall downstream supply chain performance in the range of 9-41%. Moreover, the study discovered the key functional elements of the supply chain for ICT adoption that significantly improve the overall supply chain performance. Conclusions: The study presents a definite view of the quantitative benefits of ICT adoption to the supply chain decision-makers of the retail industry and aids them in selecting appropriate functional elements for ICT adoption to maximize their supply chain performance.
Keywords: 650; feature engineering; feature selection; ICT adoption; supply chain functional elements; supply chain in the retail industry